Characteristics of non-culprit plaques in acute coronary syndrome patients with layered culprit plaque. (17th December 2019) - Russo, Michele; Kim, Hyung Oh; Kurihara, Osamu; Araki, Makoto; Shinohara, Hiroki; Thondapu, Vikas; Yonetsu, Taishi; Soeda, Tsunenari; Minami, Yoshiyasu; Higuma, Takumi; Lee, Hang; Fracassi, Francesco; et al.
Abstract: Aims : Layered plaques represent signs of previous plaque destabilization. A recent study showed that acute coronary syndrome (ACS) patients with layered culprit plaque have more vulnerability at the culprit lesion and systemic inflammation. We aimed to compare the characteristics of non-culprit plaques between patients with or without layered plaque at the culprit lesion. We also evaluated the characteristics of layered non-culprit plaques, irrespective of culprit plaque phenotype. Methods and results: We studied ACS patients who had undergone pre-intervention optical coherence tomography (OCT) imaging. The number of non-culprit lesions was evaluated on coronary angiogram and morphological characteristics of plaques were studied by OCT. In 349 patients, 99 (28.4%) had layered culprit plaque. The number of non-culprit plaques in patients with or without layered culprit plaque was similar (3.2 ± 0.8 and 2.8 ± 0.8, P  = 0.23). Among 465 non-culprit plaques, 145 from patients with layered culprit plaque showed a higher prevalence of macrophage infiltration (71.0% vs. 60.9%, P  = 0.050). When analysed irrespective of culprit plaque phenotype, layered non-culprit plaques showed higher prevalence of lipid (93.3% vs. 86.0%, P  = 0.028), thin cap fibroatheroma (29.7% vs. 13.7%, P  < 0.001), and macrophage infiltration (82.4% vs. 54.0%, P  < 0.001) than non-layered plaques. Plaques with layered phenotype at both culprit and non-culprit lesions had the highest vulnerability. Conclusion : In ACS patients, those with layered phenotype at the culprit lesion demonstrated greater macrophage infiltration at the non-culprit sites. Layered plaque at the non-culprit lesions was associated with more features of plaque vulnerability, particularly when the culprit lesion also had a layered pattern.